Hubungan Intensitas Nyeri Keluhan Muskuloskeletal dengan Kualitas Hidup Pekerja atau Buruh Kayu di Telukan Sukoharjo - Kamilah Nur Azizah; Lis Sarwi Hastuti (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: Workers in the wood industry are professions that receive daily physical burdens with risk of experiencing musculoskeletal complaints. Musculoskeletal pain is common and causes mild or severe disability in workers/labor. Musculoskeletal complaints can be caused by individual factors such as age, gender, and occupational factors such as length of time and work experience. Quality of life is an individual's perception and emotional response to the individual's position in life including physical, mental health, social relationships and the environment. Objectives: The purpose of this study was to determine the relationship between pain intensity of musculoskeletal complaints and the quality of life of workers/laborers in Telukan, Sukoharjo. Methods: This is a non-experimental quantitative research with a cross-sectional design. The research was conducted at UD. X in Telukan, Sukoharjo. The sample population of this research consisted of 30 samples. The sampling technique was carried out with a total sampling of 30 samples. Methods of collecting data by interview and filling out questionnaires using the instrument Numeric Rating Scale (NRS) and The World Health Organization Quality of Life (WHOQOL-Bref). Analysis of the data used is the Spearman Rank test. Results: The results of the analysis of the hypothesis test data were obtained r=0.542 and ρ value = 0.002 of the value (α) 0.05, which means ρ value <0.05 so that the results have a significant relationship between the pain intensity of musculoskeletal complaints and the quality of life of wood workers. Conclusion: Pain intensity of musculoskeletal complaints has a negative correlation with quality of life of wood workers in Telukan, Sukoharjo Keywords: Pain Intensity, Musculoskeletal Complaints, Quality of Life, Workers